Crabs Identification in the MangroveEcosystem, KampungMadong, KampungBugis Village, Tanjungpinang City, Riau Islands - Susanti, Lasri; Eddiwan, Eddiwan; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACK The mangrove ecosystem condition in KampungMadong waters has been damaged. Mangrove ecosystems are widely used by local communities as fishing areas. In the mangrove ecosystem inhabited by aquatic organisms such as crabs. Scientific information on crabs living in that area, however, is almost none. To understand the crabs  present in that mangrove ecosystem, a study has been conducted from March-April 2019. The crabs was captured using bento. Morphologicaland morphometriccharacteristics on the crabs captured were described based on Sakai (1976), Ng (1998) and journals relating to identification of crabs. The number of caught crab samples was 68, and they were belonge to two speciesnamelyScylla serrataand Portunuspalagicus (Portunidae). This speciesis medium sized crabs,Scylla serrata  40-105 mmcarapace width, dark green carapace colors. Portunis palagicus  40-110 mm, with carapace colors of males are blue while females are dark, in carapace have a lateral tooth or spin. Males have a bigger chela and a narrower abdomen than females.Keywords: Crabs, Portunidae, Scylla serrata, Portunus palagicus, Mangrove Ecosystem.